2019
DOI: 10.21608/jappmu.2019.40530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olive Cake Pulp as A Partial or A Complete Substitute of Wheat Bran in Growing Rabbits’ Diet on Growth Performance, Carcass Traits and Blood Constituents under North Sinai Conditions

Abstract: Sixty weaned New Zealand white rabbits of both sexes aged 6 wk and weighed 715 g were randomly divided into four treatment groups (15 rabbits each) to evaluate the possibility of feeding growing rabbits on diets containing olive cake pulp (OCP) as partial or complete substitution of wheat bran. The first group (C) was fed the basal diet as control (0%OCP), while the other three treatment groups (L, M, H) were fed diets containing 15, 20 and 25%OCP, respectively replacing wheat bran in the basal diet. All the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 2 publications
3
8
1
Order By: Relevance
“…This may be attributed to the presence of growth-promoting compounds in dates that enhance energy and protein utilization, as suggested by [64,65] resulting in a better synchrony between energy release and protein degradation, leading to increased microbial protein yield. In contrast, our research contradicts prior studies by [62,66,67,68], who found no significant variations in the live BW and BWG of rabbits fed diets containing olive by-products.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This may be attributed to the presence of growth-promoting compounds in dates that enhance energy and protein utilization, as suggested by [64,65] resulting in a better synchrony between energy release and protein degradation, leading to increased microbial protein yield. In contrast, our research contradicts prior studies by [62,66,67,68], who found no significant variations in the live BW and BWG of rabbits fed diets containing olive by-products.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, our findings were consistent with those of [61] who found that incorporating 10% of date waste meal into the diet led to better final BW compared to higher percentages such as 30% and 40%. Furthermore, [11,62] Egypt. J. Vet.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Walaa et al (2016) showed that carcass traits were significantly affected by OCM inclusion. While, Bakr et al (2019) showed that olive pulp inclusion in growing rabbits diets at varying levels (15, 20 and 25%) did not show any significant effect on all carcass traits. Similarly, Abd EL-Galil (2001) showed non-significant differences in carcass traits of rabbits fed either control or 20% olive pulp meal.…”
Section: Carcass Characteristicsmentioning
confidence: 82%
“…Salama et al (2016) showed that carcass traits were significantly affected by olive cake meal inclusion. While, Bakr et al (2019) showed that olive pulp inclusion in growing rabbits diets at varying levels (15, 20 and 25%) did not show any significant effect on all carcass traits.…”
Section: Carcass Traitsmentioning
confidence: 82%
“…Abdel-Aleem (2010) observed that plasma cholesterol concentration of growing rabbits was significantly decreased with increasing the level of NaHCO3 from 0.5 to 1%. Cholesterol was not significantly affected for rabbits fed diets containing 20, 25 and 30% OP (Mehrez and Mousa, 2011) or diet containing OCM (Bakr et al, 2019). On the other hand, olive cake up to 9% in laying hens' diets had no significant influence on serum cholesterol and triglycerides (Zangeneh and Torki, 2011).…”
Section: Blood Biochemical Analysismentioning
confidence: 99%